Simple meteor scatter out-station antennas - Givati, Ofer (My University, 2015)
T his dissertation examines simple Meteor Burst Communication (M B C) out-starioL * i-^nas. The eSect o f illum ination gain, beam w idth and orientation was studied using computer ^vr.t-iation. Sim ilarly, the performance o f M B C links using a half-wave dipole, a quarter-wave rnonopole, a square loop, a long w ue and a 5-elements Yagi-Uda antennas was determined. The performance o f these links are related to the antennas’ sky i l l umination. This investigation provides designers some bench-mark results which indicate the role played by the antennas ’ radiation patterns in M B C. A value system was formulated to provide practical and electrical trade-offs fo r m obile andmanpack antennas in the meteor scatter environment. Simulated results indicate that simple antennas cause degraded communications due to their reduced size and complexity. The conclusion is that the directional master station should provide adequate sky illumination. I t is recommended that the results obtained be validated by measurements and further work concentrate on master station antennas.
A dissertation submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, infulfilment of the requirements for the degree of Master of Science in Engineering Johannesburg, 1989
Keywords: Antennas (Electronics)